A new species of sand crab Jonas Hombron & Jacquinot, 1846 (Crustacea: Decapoda: Brachyura: Corystidae) from the southeastern coast of India - Barathkumar, S.; Das, N. P. I.; Satpathy, K. K. (Zootaxa, 2016)
A new species of sand crab of the genus Jonas Hombron & Jacquinot, 1846 (family Corystidae) is described from specimens collected from Kalpakkam, southeastern coast of India. Two other species, J. indicus (Chopra, 1935), and J. choprai Serène, 1971, have previously been recorded from this area. A detailed description of the new species is given and compared with the closely related J. formosae Balss, 1922, also from the Indo-West Pacific.